2015
DOI: 10.1371/journal.pone.0129204
|View full text |Cite
|
Sign up to set email alerts
|

The Low Proportion and Associated Factors of Involuntary Admission in the Psychiatric Emergency Service in Taiwan

Abstract: BackgroundThe involuntary admission regulated under the Mental Health Act has become an increasingly important issue in the developed countries in recent years. Most studies about the distribution and associated factors of involuntary admission were carried out in the western countries; however, the results may vary in different areas with different legal and socio-cultural backgrounds.AimsThe aim of this study was to investigate the proportion and associated factors of involuntary admission in a psychiatric e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 39 publications
(83 reference statements)
1
18
1
Order By: Relevance
“…Our findings of increased likelihood with adversarial routes such as police contacts 10 , 41 , 44 and decreased likelihood with physician contact 7 are consistent with the international literature. We also found independent associations between past year mental health visits and visits on the pathway to care, both with decreased likelihood of involuntary admissions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings of increased likelihood with adversarial routes such as police contacts 10 , 41 , 44 and decreased likelihood with physician contact 7 are consistent with the international literature. We also found independent associations between past year mental health visits and visits on the pathway to care, both with decreased likelihood of involuntary admissions.…”
Section: Discussionsupporting
confidence: 91%
“…The only exception to higher likelihood of involuntary admissions with greater severity was the lower likelihood of involuntary admission with higher ratings of depression measured by the DRS, which has been found in other studies and has been suggested to reflect greater levels of insight. 44 The set of factors included in this study is more diverse and extensive than that used in most previous studies, 7 , 8 , 10 , 12 , 41 , 44 but the general finding of greater likelihood of involuntary admissions with greater severity is a consistent finding among studies.…”
Section: Discussionmentioning
confidence: 85%
“…In Taiwan, the Mental Health Act, introduced in 1990 and amended in 2007, legally defined the criteria for involuntary treatment as a patient in a psychotic state who is unable to adhere to treatments and is a danger to themselves or others (62). Compulsory hospitalization for severe mental illness should be determined by two designated psychiatrists (63).…”
Section: Resultsmentioning
confidence: 99%
“…However, most studies to date on the distribution and associated factors of involuntary admission have been carried out in the Western countries. Although the results may vary in different areas according to their particular legal and sociocultural backgrounds, there are very few studies providing data about involuntary admissions in Asian countries despite their highly variable results [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Across the European Union around 30%-50% of involuntary admissions are reported to be attributed to schizophrenia and related psychotic conditions [ 1 , 2 , 6 ]. More recent evidence in Taiwan also shows a very high proportion, 72%, of involuntary admissions being due to diagnoses of psychotic disorders [ 5 ]. Indeed, previous studies have indicated that patients diagnosed with psychotic disorders [ 7 10 ], especially schizophrenia [ 11 13 ], are more likely to be involuntarily admitted.…”
Section: Introductionmentioning
confidence: 99%